Dinner in the dark: Factors influencing leopard activity patterns within a large protected area - Lucy K. Smyth; Guy A. Balme; M. Justin O’Riain (PLoS ONE, 2025)
Spatial avoidance is one of the most pervasive responses of wildlife to human disturbance, but new research is increasingly revealing the importance of temporal shifts in activity. Animal species appear to become more nocturnal in areas with greater levels of human disturbance given the predominantly diurnal nature of anthropogenic activity. Here we investigate the relative importance of anthropogenic (relative abundance of pedestrians only, vehicles only and humans on foot and in vehicles combined, artificial light at night and distance to reserve edge or human settlements) and ecological (relative abundance of potential prey and potential competitors, temperature, season and lunar light) factors on the activity patterns of leopards (Panthera pardus) in the greater Kruger National Park (KNP) region of southern Africa. We use independent captures from camera trap data collected across 10 sites in and around central and southern KNP as an index of leopard activity, and kernel density models to estimate activity patterns of leopards. No differences in overall leopard activity levels were evident between sites but activity patterns within a 24-hour period differed. These differences were best explained by the relative abundance of pedestrians, with the relative abundance of all humans (on foot or in a vehicle) affecting timing of leopard activity almost as strongly, followed by the relative abundance of vehicles. Leopard activity also varied significantly with the lunar cycle, peaking around full moon. These results suggest that diel leopard activity patterns in South Africa’s largest protected area are primarily driven by anthropogenic not environmental factors, though moonlight is important on the lunar scale. The sensitivity of leopard activity to nocturnal illumination from the moon urges caution regarding levels of human induced artificial light at night which are increasing globally, and could reach a threshold at which they begin to affect leopard activity patterns.